UTX/KDM6A deletion promotes the recovery of spinal cord injury by epigenetically triggering intrinsic neural regeneration - Zhu Guo; Chengjun Li; Yong Cao; Tian Qin; Liyuan Jiang; Yan Xu; Miao Li; Zixiang Luo; Jianzhong Hu; Hongbin Lu (Molecular Therapy: Methods & Clinical Development, 2021)
Interrupted axons that fail to regenerate mainly cause poor recovery after spinal cord injury (SCI). How neurons epigenetically respond to injury determines the intrinsic growth ability of axons. However, the mechanism underlying epigenetic regulation of axonal regeneration post-SCI remains largely unknown. In this study, we elucidated the role of the epigenetic regulatory network involving ubiquitously transcribed tetratricopeptide repeat on chromosome X (UTX)/microRNA-24 (miR-24)/NeuroD1 in axonal regeneration and functional recovery in mice following SCI. Our results showed that UTX was significantly increased post-SCI and repressed axonal regeneration in vitro. However, downregulation of UTX remarkably promoted axonal regeneration. Furthermore, miR-24 was increased post-SCI and positively regulated by UTX. miR-24 also inhibited axonal regeneration. Chromatin immunoprecipitation (ChIP) indicated that UTX binds to the miR-24 promoter and regulates miR-24 expression. Genome sequencing and bioinformatics analysis suggested that NeuroD1 is a potential downstream target of UTX/miR-24. A dual-luciferase reporter assay indicated that miR-24 binds to NeuroD1; moreover, it represses axonal regeneration by negatively regulating the expression of NeuroD1 via modulation of microtubule stability. UTX deletion in vivo prominently promoted axonal regeneration and improved functional recovery post-SCI, and silencing NeuroD1 restored UTX function. Our findings indicate that UTX could be a potential target in SCI.